200 NL H2 hydrogen storage tank using MgH2–TiH2–C nanocomposite as H storage material. (25th May 2021) - Nyallang Nyamsi, Serge; Lototskyy, Mykhaylo V.; Yartys, Volodymyr A.; Capurso, Giovanni; Davids, Moegamat Wafeeq; Pasupathi, Sivakumar
Abstract: MgH2 -based hydrogen storage materials are promising candidates for solid-state hydrogen storage allowing efficient thermal management in energy systems integrating metal hydride hydrogen store with a solid oxide fuel cell (SOFC) providing dissipated heat at temperatures between 400 and 600 °C. Recently, we have shown that graphite-modified composite of TiH2 and MgH2 prepared by high-energy reactive ball milling in hydrogen (HRBM), demonstrates a high reversible gravimetric H storage capacity exceeding 5 wt % H, fast hydrogenation/dehydrogenation kinetics and excellent cycle stability. In present study, 0.9 MgH2 + 0.1 TiH2 +5 wt %C nanocomposite with a maximum hydrogen storage capacity of 6.3 wt% H was prepared by HRBM preceded by a short homogenizing pre-milling in inert gas. 300 g of the composite was loaded into a storage tank accommodating an air-heated stainless steel metal hydride (MH) container equipped with transversal internal (copper) and external (aluminium) fins. Tests of the tank were carried out in a temperature range from 150 °C (H2 absorption) to 370 °C (H2 desorption) and showed its ability to deliver up to 185 NL H2 corresponding to a reversible H storage capacity of the MH material of appr. 5 wt% H. No significant deterioration of the reversible H storage capacity was observed during 20 heating/cooling H2 discharge/charge cycles. It was found that H2 desorption performance can be tailored by selecting appropriate thermal management conditions and an optimal operational regime has been proposed. Highlights: Upscaled synthesis of MgH2 –TiH2 –graphite H storage nanocomposite performed. The nanocomposite (300 g; storage capacity 6.3 wt %H) used to build H2 storage tank. Fast H2 charge of the tank proceeds at T ≥ 150 °C and P(H2 ) = 5–10 bar. At T = 370–390 °C the tank is able to provide 185 NL H2 (5 wt% H) with P(H2 ) = 2 bar. H2 discharge performance is very sensitive to the thermal management conditions.